EFL TEACHERS’ ATTITUDES ON GENDER DIFFERENCES IN SCHOOL ACHIEVEMENTS - Belaid, Louiza; Sarnou, Hanane (LLT Journal: A Journal on Language and Language Teaching, 2019)
This work assesses the perspectives of teachers on pupils? classroom performance in a foreign language. Its objectives target to discover the challenges that educators face in teaching English. English is a foreign language that teachers encounter difficulties to teach especially to a population whereby their linguistic background does not help in using the language properly. In this prospect, our research questions search for the obstacles that hinder the teachers of English from receiving a positive feedback from their pupils? performance. As a research tool, a questionnaire is handed to forty six teachers in Tissemsilt-Algeria. The results exhibit weaknesses in dealing with pupils especially in using the language in an oral or a written task, besides the violent behaviour of males in the classroom which represents a hindrance for educators to manage the classroom, communicate and teach effectively.DOI: 10.24071/llt.2019.220203